Intelligence between knowledge and ignorance, between acceptance and rejection - Lupu, Mădălina-Elena (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
This article focuses on intelligence being between knowledge and ignorance, between acceptance and rejection and uses it as a research method the historical and comparative analysis. It begins with an overview of intelligence importance in the security policy of states resulting from history and continues with the analysis of knowledge versus ignorance of the historical role of intelligence. It ends with a comparative analysis of prominent political leaders such as Winston Churchill (Great Britain), Dwight Eisenhower (United States), Joseph Stalin (Union of Soviet Socialist Republics) and Adolf Hitler (Germany), not from the perspective of the positive or negative influence they have had, but from the perspective of using versus not using intelligence in the decision-making process. It shows that reducing the distance between ignorance and knowledge depends on human will, history being right behind us or in front of us, depending on how we look at it. It also shows that the acceptance of intelligence in the decision making process depends on human factors too, intelligence being right in front of policymakers, depending on if they understand intelligence value and if they believe more in intelligence than in themselves when it comes to national security.